Particulate matter (PM 2.5) at construction site: a review - Rosman, Putri Shazlia; Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Mohd Hussain, Mohd Ramzi (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
In Malaysia, construction sector growing 8% to RM170 billion in 2017, 8.2 % or RM140 billion in 2015 and 7.4% t or RM166 billion in 2016.Construction activities at all phases ofconstruction from land clearing to building structure generate particulate matter emission (PM) that causes health impact to human and environment. Many researchers have done to identify and classified the particulate matter from its source of origins emissions at construction site. PM2.5 is a fine particle is potential to enter lung and bloodstream and lead to death. The objective of this paper to identify the potential of PM2.5 release at construction site, effect to receptor who exposed to it and determine the other factor that contribute to distribute the PM2.5 at construction site. The construction activity proved to cause PM2.5 emission effect to human health and environment. Though, meteorology such as wind direction, temperature, humidity, pressure, wind speed not only factor need to be considerate that influences the distribution dispersion of PM2.5 but other factor such as chemical formation, dispersion process and removal mechanism need to be measured. CDC 2013 studies, showed every PM2.5 decreases of 10 ug/m3 of air it will decrease 15% in the risk of heart disease deaths. Malaysia showed the annual mean concentration of fine particulate matter in urban areas was exceeding the WHO air quality guideline with 17.3 ug/m3. The construction site needs to control and monitored its emission of particulate matter by having a proper schedule construction time management and modeling the distribution of PM2.5 at site.